2012
DOI: 10.1002/lary.23327
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological aspects of recurrent respiratory papillomatosis: A population‐based study

Abstract: Objectives/Hypothesis:The incidence of genital infections, cervical cancer, and oropharyngeal cancer induced by human papillomaviruses (HPV) is increasing in Western countries. Primarily, this study was conducted to estimate the incidence rate of recurrent respiratory papillomatosis (RRP) in juveniles and adults in two Norwegian subpopulations for each year between 1987 and 2009. The secondary objective of the study was to investigate whether there are trends in the incidence rates of RRP in the study period s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
39
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 24 publications
9
39
0
1
Order By: Relevance
“…There is no surveillance of genital warts in Norway as there is in the UK and USA, but similar trends are reported in Scandinavia for both genital warts [23] and oropharyngeal carcinomas [24], [25]. It is reasonable to expect similar trends in RRP, but currently we have no evidence of such [8], [9].…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…There is no surveillance of genital warts in Norway as there is in the UK and USA, but similar trends are reported in Scandinavia for both genital warts [23] and oropharyngeal carcinomas [24], [25]. It is reasonable to expect similar trends in RRP, but currently we have no evidence of such [8], [9].…”
Section: Introductionmentioning
confidence: 73%
“…The condition is rare [7][9] and characterized by recurrent growth of benign papillomas in the respiratory tract, most commonly in the larynx [10], [11]. According to the age at onset, two types of RRP are recognized; juvenile- (JoRRP) and adult-onset (AoRRP).…”
Section: Introductionmentioning
confidence: 99%
“…The infection is believed to be acquired from the mother's genital tract during the birthing process [1]. Although the estimated incidence and prevalence of JORRP has been determined in countries in North America and Europe and in Australia [2][3][4][5][6][7][8][9][10], there have not been any studies that have attempted to determine the incidence or prevalence of JORRP in African countries.…”
Section: Introductionmentioning
confidence: 98%
“…Papillomatosis in other sites of the body show a female predominance for genital (33% vs 67%) and cutaneous (49% vs 51%) papillomas and a male predominance for upper respiratory involvement (77% vs 23%). 24,[26][27][28] Multicentric conjunctival papillomas were more common in children and adolescents than in adults, and the numerous lesions coalesced to form massive papillomatosis in 1 patient ( Figure 1B). Ash 17 studied 245 conjunctival papillomas in patients of all ages (range, 1-97 years) and found that the most common location of conjunctival papilloma was the bulbar conjunctiva (42%).…”
Section: Commentmentioning
confidence: 99%